Chemical profiles of the active fraction from Prinsepia utilis Royle leaves and its anti-benign prostatic hyperplasia evaluation in animal models - Ying Peng; Chongsheng Peng; Yang Wu; Chongzhi Sun; Xiaobo Li (BMC Complementary Medicine and Therapies, 2021)
Abstract Background The Prinsepia utilis Royle leaves (P. utilis) is a folk herb used for benign prostatic hyperplasia (BPH) control by ethnic minorities for centuries in China with rich in resources. Our previous studies have confirmed the anti-BPH effect of its water extract (QCJ) and the active fraction (Fr. B) separated from the QCJ by animal test. The Fr. B from P. utilis should be a potential candidate for BPH control. Methods In this study, the chemical ingredients of Fr. B were identified by UPLC-QTOF-MS, and quantified by HPLC. Murine animal models were divided into 8 groups, Sham rats, BPH rats, BPH rats administered with finasteride (1 mg/kg), BPH rats administered with Pule’an (460 mg/kg), BPH rats administered with low, high dosage of QCJ (860 mg/kg, 2580 mg/kg respectively), BPH rats administered with low, high dosage of Fr. B (160 mg/kg, 480 mg/kg respectively). The expression of vascular endothelial growth factor (VEGF) in the prostate tissue of rats was tested, and serum levels of dihydrotestosterone (DHT), testosterone (T), estradiol (E2), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and total superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), malondialdehyde (MDA) in prostate homogenate were measured. One-way ANOVA followed by LSD was used for statistical analysis. Results The BPH rats treated by Fr. B exhibited significant reductions of VEGF and MDA levels, as well as significant increases of SOD, GSH-Px and CAT in the prostate tissue after 28 day administration (P < 0.05). Moreover, Fr. B significantly reduced DHT, DHT/E2 ratio, TNF-α, while increased T levels in serum of BPH rats (P < 0.05). UPLC-QTOF-MS analysis revealed 10 flavonoids as the key constituents of this fraction, which accounted for 54.96% of all substance of Fr. B. The relative contents of compound 1, 2 are 11.1%, 13% in Fr. B respectively. Conclusions These results indicated that the Fr. B obtained from P. utilis alleviated the symptoms of BPH rats through multiple mechanisms including reduction of DHT/E2 ratio, inhibition of growth factor, anti-inflammation and anti-oxidation, in which flavonoids might be the key constituents. It supported the hypothesis that the Fr. B should be further explored as a candidate for BPH patients.